Skeletal adaptation to mechanical cues during homeostasis and repair: the niche, cells, and molecular signaling - Atria, Pablo J.; Castillo, Alesha B. (Frontiers in Physiology, 2023)
Bones constantly change and adapt to physical stress throughout a person's life. Mechanical signals are important regulators of bone remodeling and repair by activating skeletal stem and progenitor cells (SSPCs) to proliferate and differentiate into bone-forming osteoblasts using molecular signaling mechanisms not yet fully understood. SSPCs reside in a dynamic specialized microenvironment called the niche, where external signals integrate to influence cell maintenance, behavior and fate determination. The nature of the niche in bone, including its cellular and extracellular makeup and regulatory molecular signals, is not completely understood. The mechanisms by which the niche, with all of its components and complexity, is modulated by mechanical signals during homeostasis and repair are virtually unknown. This review summarizes the current view of the cells and signals involved in mechanical adaptation of bone during homeostasis and repair, with an emphasis on identifying novel targets for the prevention and treatment of age-related bone loss and hard-to-heal fractures.PAGE \* Arabic \* MERGEFORMAT 3 damaged bones. SSPCs reside in a specialized microenvironment known as the niche which acts as the central hub for maintaining cellular identity during quiescence and coordinating a response to mechanical and biological signals. In bone, SSPCs have been found in the periosteum, endosteum, marrow and growth plate. (11)(12)(13)(14)(15)(16) Current FDA approved anabolic treatments that can prevent bone loss are Teriparatide, Abaloparatide and Romosozumab. The first two are PTH analogs, while Romosozumab is a sclerostin inhibitor. All of these medications suppress bone remodeling, and might have an effect on the cellular populations which line the bone surface,(17, 18) even though this process has not been fully understood. Therefore, understanding the mechanisms involved in SSPC niche regulation is crucial for developing therapeutic strategies to prevent and treat skeletal disease and injury. This review focuses on the identity of murine SSPCs, their unique environment in different bone compartments, and their involvement in bone homeostasis and repair. We then describe the mechanical environment in bone, relying heavily on previous comprehensive reviews by the senior author, with emphasis placed on the interplay between the niche, SSPCs and their response to mechanical signals during homeostasis and repair.